2019
DOI: 10.1177/1045389x19888722
|View full text |Cite
|
Sign up to set email alerts
|

Strain sensitivity of steel-fiber-reinforced industrial smart concrete

Abstract: Self-sensing cementitious composites can enable structures that are capable of carrying the loads applied on them while monitoring their condition. Most of earlier research has focused on the incorporation of nanofillers or microfibers into cement paste or mortar composites. However, there have been very limited number of studies on the development of steel-fiber-reinforced cementitious composites with self-sensing capabilities. This study explores strain sensitivity of concrete mixtures that include coarse ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In a different study, Monteiro et al [10] suggested that the optimal amount of carbon black to improve both mechanical and electrical properties of concrete containing is 7%. Together, these studies demonstrate that the incorporation of conductive materials into concrete may enable structural health monitoring (SHM) and vehicle detection of civil infrastructure [1,3,11].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a different study, Monteiro et al [10] suggested that the optimal amount of carbon black to improve both mechanical and electrical properties of concrete containing is 7%. Together, these studies demonstrate that the incorporation of conductive materials into concrete may enable structural health monitoring (SHM) and vehicle detection of civil infrastructure [1,3,11].…”
Section: Introductionmentioning
confidence: 89%
“…As concrete technology improves, concrete structures are lasting longer and are subject to material deterioration and changing environments, including climate [1][2][3]. Environmental and structural stressors shorten the life of concrete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The self-sensing ability of concrete is achieved by a change in the conductive network of the conductive material inside the concrete (Al-Dahawi et al, 2016a;Al-Dahawi et al, 2016b;Al-Dahawi et al, 2017;Yıldırım et al, 2018;Demircilioğlu et al, 2019;Yıldırım et al, 2020). Smart concrete is developed by adding carbon nanotube (Xing et al, 2016;Al-Dahawi et al, 2017;Gupta et al, 2017;Yoo et al, 2017;Yıldırım et al, 2018;Lee et al, 2020;Yıldırım et al, 2020), carbon fibers (Al-Dahawi et al, 2017;Yıldırım et al, 2018;Yıldırım et al, 2020), steel fibers (Le and Kim, 2017;Demircilioglu et al, 2020;Le and Kim, 2020), graphite nanofibers (Yoo et al, 2017), graphene (Al-Dahawi et al, 2016a;Al-Dahawi et al, 2016b;Al-Dahawi et al, 2017;Yoo et al, 2017;Birgin et al, 2020;Wang et al, 2020), nickel or hybrid materials (Azhari and Banthia, 2012;Konsta-Gdoutos and Aza, 2014) and other functional fillers. The research on CNT reinforced self-sensing cement-based materials is the most concentrated.…”
Section: Introductionmentioning
confidence: 99%